2013
DOI: 10.1186/1743-422x-10-81
|View full text |Cite
|
Sign up to set email alerts
|

Foot-and-mouth disease virus carrier status in Bos grunniens yaks

Abstract: BackgroundThe carrier status of foot-and-mouth disease virus (FMDV) is complicated, and the role of carrier animals in virus transmission is controversial. To investigate the carrier status of FMDV in animals that live in high altitude, Bos grunniens yaks were infected experimentally with FMDV O/Akesu/58.ResultsAll of the yaks showed clinical signs of foot-and-mouth disease (FMD). Total antibody levels against FMDV measured by liquid-phase blocking enzyme-linked immunosorbent assay (LPB-ELISA) and antibody lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, in the same model, further studies showed that persistent FMDV evolves to induce a more intense shut-off of host-cell protein expression [24]. Viral mutations of FMDV during persistence, leading to antigenic variation, have been proposed to be among the key factors in the establishment and maintenance of persistence of infection in vivo [11,16,20,36]. Interestingly, sequencing the VP1 coding region of virus isolated from persistently infected cattle or water buffalo reveals modifications of only 2 to 6 amino acids, targeting mostly residues 40-50 and 135-151 [7,20].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, in the same model, further studies showed that persistent FMDV evolves to induce a more intense shut-off of host-cell protein expression [24]. Viral mutations of FMDV during persistence, leading to antigenic variation, have been proposed to be among the key factors in the establishment and maintenance of persistence of infection in vivo [11,16,20,36]. Interestingly, sequencing the VP1 coding region of virus isolated from persistently infected cattle or water buffalo reveals modifications of only 2 to 6 amino acids, targeting mostly residues 40-50 and 135-151 [7,20].…”
Section: Discussionmentioning
confidence: 93%
“…The FMDV carrier state has been clearly demonstrated in ruminants, particularly in bovine species (wild as well as domestic) [2,11,33,50]. We therefore sought to develop an in vitro model to study cellular and/or viral determinants of FMDV persistence, using a bovine epithelial cell line, the Madin-Darby bovine kidney (MDBK) cell line.…”
Section: Introductionmentioning
confidence: 99%
“…Most cattle carry foot-and-mouth disease virus (FMDV) for six months or less, but some animals can remain persistently infected for up to 3.5 years [ 4 , 5 ]. The virus or its nucleic acids have been found for up to 12 months in sheep, up to 4 months in goats, for a year in water buffalo, and up to 8 months in yaks [ 7 ]. Carrier animals can only be identified by collecting esophageal-pharyngeal fluids for virus isolation and/or the detection of nucleic acids.…”
Section: Introductionmentioning
confidence: 99%
“…Self-recovery is the result of immunity against the serotype of the virus. Mostly, FMD occurs due to one type of virus and immunity remain limited against specific serotype, thus no immunity develops against another serotypes, so in endemic areas, it is the main reason behind occurrence of disease[31]. In most extreme cases, mortality in lambs and suckling pigs ranges from 20-75% and it depends on age.…”
mentioning
confidence: 99%